The Implementation of School from Home in English for Young Learners' Classrooms - Azharra Aninda Putri Al Farid; Ika Lestari Damayanti (Universitas Pendidikan Indonesia, 2022)
The sudden occurrence of the coronavirus pandemic (COVID-19) has affected the education sector in Indonesia. The Indonesian government responded to this matter and issued a policy on the implementation of distance learning or known as the school from home. School from home has been applied to all education levels in Indonesia, including primary schools. This qualitative case study investigates the implementation of school from home in English for young learners' classrooms at a primary school in Indonesia. The data was collected through online classroom observation in second, fourth, and sixth-grade classrooms and interviews with five English teachers who taught in first until sixth-grade classrooms. Data from the interview were analyzed using thematic analysis, resulting in three generated themes on the implementation of school from home in English for young learners' classrooms. The themes include teachers' readiness to implement school from home, teachers' strategies to implement online learning as part of the school from home, and teachers' strategies to overcome challenges in online learning. The results of the study indicated that the implementation of school from home requires thorough preparation and has the potential to be implemented in English for young learners' classrooms, especially in the upper-grade classrooms of primary schools.